2013
DOI: 10.15376/biores.8.2.2145-2160
|View full text |Cite
|
Sign up to set email alerts
|

Production of Mesoporous Activated Carbon from Tea Fruit Peel Residues and Its Evaluation of Methylene Blue Removal from Aqueous Solutions

Abstract: Removal of methylene blue by activated carbon produced from tea fruit peel (Camellia sinensis L.) residue using agents ZnCl 2 (AC-1) and H 3 PO 4 (AC-2) was investigated in this work. Mesoporous activated carbons with desirable surface areas and total pore volumes were obtained. Meanwhile, the characteristics of the activated carbon were examined. The effects of solution pH (2 to 10), contact time (0 to 480 min), and adsorbate dosage (0.5 to 3.5 g L -1) were studied. Equilibrium adsorption data were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 32 publications
0
14
2
1
Order By: Relevance
“…The suitability of the PSO kinetic model indicated that the step that controls the adsorption rate was mainly chemical sorption. The PSO kinetic model also indicated that the colour, TSS and COD adsorption rates were affected more by the number of available adsorption sites on the CSAC surface than the effect of POME solution concentration [21]. The adsorption rate was governed by a second-order rate law.…”
Section: Adsorption Kinetics Studymentioning
confidence: 95%
“…The suitability of the PSO kinetic model indicated that the step that controls the adsorption rate was mainly chemical sorption. The PSO kinetic model also indicated that the colour, TSS and COD adsorption rates were affected more by the number of available adsorption sites on the CSAC surface than the effect of POME solution concentration [21]. The adsorption rate was governed by a second-order rate law.…”
Section: Adsorption Kinetics Studymentioning
confidence: 95%
“…The findings showed that the step controlling adsorption rate of CBA-HCl was chemical sorption and POME colour adsorption rate was affected by the number of available adsorption sites on the surface of CBA-HCl rather than POME solution concentration. 41,42 Table 5 shows the respective q e , K 1 of first order adsorption, and K 2 of pseudo second order adsorption.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Researchers have developed alternatives for biomass from agricultural waste such as flax shives (MARSHALL et al, 2007), rice stalk (AI et al, 2013), rice straw (HU; HSIEH, 2014), orange peel (KÖSEOĞLU; AKMIL-BAŞAR, 2015), cotton stalk (NAHIL; WILLIAMS, 2012), cocoa shell (AHMAD et al, 2013), grape stalk (DEIANA et al, 2009), apple peel (HESAS et al, 2013), and tea fruit peel (GAO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%